2007
DOI: 10.1007/bf03326300
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cd concentration of crude oil polluted arable soils

Abstract: Thirty soil samples were analyzed for their properties and cadmium concentration in polluted and unpolluted sites of Isikwuato, Abia State, Nigeria. Polluted soils were more acidic (pH = 4.38) than unpolluted ones (pH = 5.22). Bulk density increased in polluted soils (1.51 g/cm 3 ). Higher average value of organic matter was recorded in polluted soils (mean value = 1.42 %) unlike 0.98 % found in unpolluted soils. Cadmium concentration was higher in polluted soils (0.76 mg/kg) contrasting with 0.02 mg/kg obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…al., 2015). The result of this study revealed that the soils were more of sand, followed by silt and least in clay as earlier reported by Onweremadu and Duruigbo (2007). Hence, the high sand content encouraged leaching of heavy metals deep down into the soil depth due to the larger pore size (Akpoveta et.…”
Section: Enerijiofi Et Al: Assessment Of the Impact Of Cassava Mill supporting
confidence: 69%
“…al., 2015). The result of this study revealed that the soils were more of sand, followed by silt and least in clay as earlier reported by Onweremadu and Duruigbo (2007). Hence, the high sand content encouraged leaching of heavy metals deep down into the soil depth due to the larger pore size (Akpoveta et.…”
Section: Enerijiofi Et Al: Assessment Of the Impact Of Cassava Mill supporting
confidence: 69%
“…Soils suffer from pollution (Onweremadu and Duruigbo, 2007) such as crude oil spillage. Crude oil which is abundantly located in the Niger-Delta region of Nigeria is spilled on soils due to several factors such as pipeline destruction (Nwilo and Badejo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Onweremadu and Duruigbo (2007) reported significant levels of heavy metals in soils that were contaminated with automobile waste oil. Zinc though a heavy metal is also micronutrient (Alvarez-Benedi and Munoz-Carpena, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Existence of easily soluble Cd compounds in plant tissues indicates the importance of sap in Cd studies (Roosens et al, 2003). Onweremadu and Duruigbo (2007) reported that Cd is considered one of the most important environmental pollutants in agricultural soils because of the potential harmful effects it may have on food quality Abstract: Conspicuous vegetation entities of pedogenic soils rich in cadmium and their diethylene triamine pentaacetic acid (DTPA)-extractable Cd content (DCd) under the temperate continental and Mediterranean climatic conditions of western Anatolia were determined. Foliage of herbaceous plants and nearby soil samples was collected from 51 zinc mining areas.…”
Section: Introductionmentioning
confidence: 99%